Interação abelha-planta em sistemas agrícolas: forças de interação e nichos tróficos - Carvalho, Danielle Mendes (2013)
Different strategies of resource exploitation can lead to divergences in species niche realized. Niche differentiation may involve several niche dimensions, which can differ, especially in the diet, in space, and time. In this study, we measured the redundancy level or complementarity in the interaction network in a bee community associated with an agricultural system. The hypothesis is that the degree of trophic overlap on the diet axis in the community is low, with high complementarity, since there is difference in the resource supply over the vintages and, that the overlap on time axis is high with high redundancy at the time of the use of floral resources. The overlap niche on diet axis was low (NOih = 0.18) and 88% of pairs showed overlap values below 30%. Niche overlap on time axis was intermediate (NOih = 0.49), and 65% of pairs showed overlap values between 30 and 60%. The network analysis showed that the bees separate its niche on diet axis and presented additional intermediate specialization (H2 '= 0.46). And on the time axis (H2 '= 0.12) bees were considered generalists, with high temporal redundancy. When we tested whether environmental requirements determined the high redundancy at the time of use of floral resources, we verified that the temperature was not a guiding factor to structure the niche overlap in relation to the time of use. The results indicate that the low niche overlap on the diet axis and the intermediate overlap on the time axis should be reflecting the plurality of floral resources choices by different bee species, which used broad resource spectrum.